2010
DOI: 10.1111/j.1365-2796.2010.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of regulatory T cells in mediating the atheroprotective effect of apolipoprotein B peptide vaccine

Abstract: Objectives. Autoimmune responses against oxidized low-density lipoprotein are considered to play an important pro-inflammatory role in atherosclerosis and to promote disease progression. T-regulatory cells (Tregs) are immunosuppressive cells that have an important part in maintaining self-tolerance and protection against autoimmunity. We investigated whether aBp210, a prototype atherosclerosis vaccine based on a peptide sequence derived from apolipoprotein B, inhibits atherosclerosis through the activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 48 publications
4
57
0
1
Order By: Relevance
“…In previous studies, intranasal inoculation with HSP65 or an apolipoprotein B-100 peptide or oral feeding with ␤2-glycoprotin I resulted in some degree of amelioration of atherosclerosis that correlated with indications of increased IL-10 expression (9,(12)(13)(14). However, none of these studies demonstrated a causative role for IL-10 in the induction of immune tolerance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In previous studies, intranasal inoculation with HSP65 or an apolipoprotein B-100 peptide or oral feeding with ␤2-glycoprotin I resulted in some degree of amelioration of atherosclerosis that correlated with indications of increased IL-10 expression (9,(12)(13)(14). However, none of these studies demonstrated a causative role for IL-10 in the induction of immune tolerance.…”
Section: Discussionmentioning
confidence: 91%
“…Recognition of the autoimmune aspects of atherosclerosis has suggested the possibility of employing immunomodulatory approaches to ameliorate symptoms. That such an approach is feasible has been borne out in studies in which blockage of T cells reactive to native lipoprotein ApoB100 (4) or mucosal or subcutaneous immunization with HSP65 (9, 10), oxidized LDL (11), native ␤2-glycoprotein I (12), or apolipoprotein B-100 peptide (13,14) have been shown to be atheroprotective. Collagens can compose up to 60% of the total protein content in atherosclerotic plaques (15) and stimulate the growth and inflammation of atheromas (16).…”
mentioning
confidence: 99%
“…Autoimmunity against selfantigens, such as oxidized LDL and heat shock proteins (HSPs), play an important role in the development of atherosclerosis and immunization with HSPs or apoB peptides are associated with a decrease in atherosclerosis development (50,51). Atherosclerosis protection achieved by immunization with apoB peptide and Alum adjuvant has been credited to regulatory T cell dependent mechanisms (52,53). Similarly, oral administration of oxidized LDL or HSP60 is associated with increased number of regulatory T cells and reduced atherosclerosis (46,54).…”
Section: Emerging Therapies Promoting Regulatory T Cell Responsesmentioning
confidence: 99%
“…Ablation of CD25 + T-cells by CD25-depleting antibody abrogated the atheroprotective effects of subcutaneous infusion of apoB-100 peptides, similar to the study by Wigren and colleagues. 21 Taking these reports together, immunization with p210 clearly elicited a CD4 + T-cell response (be it induction of CD4 + CD25 + or CD4 + IL-10 + T-cells). How such CD4 + T-cell response is elicited or whether these CD4 + T-cells directly mediate the atheroprotective effect of p210 immunization remains unknown.…”
Section: From Low-density Lipoprotein To Apob-100-derived Peptides Asmentioning
confidence: 99%
“…Administration of antibodies against CD25 reduced CD4 + CD25 + T-cells and abrogated the atheroprotective effect of p210 immunization. 21 Immunization of female apoE -/-mice intranasally with a recombinant protein consisting of p210 fused with the cholera toxin B (CTB) subunit (p210-CTB) reduced atherosclerosis in aortic sinuses of mice when compared with control mice. The rationale of using CTB conjugated with p210 was based on (1) CTB promotes the uptake of the antigen via the nasal mucosa to elicit protective immunity; (2) CTB-based vaccines have now been tested in a first human phase II trial in Behcet's disease.…”
Section: From Low-density Lipoprotein To Apob-100-derived Peptides Asmentioning
confidence: 99%